Preparation method of ion exchange resin permanent magnetic material for high-speed water treatment process
In the magnetic iron oxide preparation process, γ-Fe2O3 is prepared by using the metathesis reaction of carbonate and ferrous salt, which solves the problem that the product in the prior art is paramagnetic iron tetroxide, and the preparation of high-purity γ-ferrous oxide is realized. It is suitable for high-speed water treatment processes and simplifies the process flow.
Patent Information
- Application Number
- CN202411867702.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-01
AI Technical Summary
In the existing preparation methods for magnetic iron oxide, most of the products are paramagnetic iron tetroxide, which has a small magnetic susceptibility and cannot maintain magnetic properties. The process is complex and costly, so it is not suitable for high-speed water treatment processes.
The activated ferrous carbonate is obtained by metathesis reaction of the carbonate solution and the ferrous salt solution, and the activated ferrous carbonate is calcined until it is completely decomposed into active ferrous tetraoxide, and the oxidation reaction is carried out at a suitable temperature to control the conversion of Fe3O4 to γ-Fe2O3.
The obtained γ-iron oxide has high purity and is easy to modify in the preparation process of magnetic ion exchange resin. It is suitable for high-speed water treatment process of suspended reaction layers. It is simple in process and easy to operate, and is suitable for large-scale production.
Smart Images

Figure CN119735239A_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a method for preparing a permanent magnetic material of an ion exchange resin in a high-speed water treatment process, relates to a method for preparing a permanent magnetic material, belongs to the technical field of water treatment, and particularly relates to a method for preparing a permanent magnetic material by obtaining active ferrous carbonate by double decomposition reaction between a carbonate solution and a ferrous salt solution, calcining the active ferrous carbonate until the active ferrous carbonate is completely decomposed into active ferroferric oxide, causing the active ferroferric oxide to undergo oxidation reaction at a suitable temperature, and controlling Fe3O4 to be completely converted into gamma-Fe2O3. Background Art
[0002] In the process of high-speed water treatment using a suspended reaction layer, magnetic ion exchange resin plays an important role in reducing the contact time between water and resin and improving water treatment efficiency. Specifically, raw water enters the bottom of the high-speed reactor from the water inlet pipe through the guide pipe. The water and resin in the reactor are stirred at a low speed by the stirrer. Due to the unique agglomeration ability of the magnetic resin, the resin can be quickly precipitated and separated. After the magnetic agglomeration force and stirring action of the resin reach a balance, a stable suspended reaction layer is formed to allow water and resin to completely contact and react to complete ion exchange. The magnetic ion exchange resin contains a permanent magnetic material - γ-iron oxide, which makes the magnetic ion exchange resin magnetic after being magnetized by the magnetizing equipment. The current preparation methods of γ-iron oxide include solid phase synthesis, sol-gel method, mechanical ball milling method and chemical co-precipitation. Co-precipitation method, etc., wherein the co-precipitation method is a method of adding a precipitant to a metal salt solution to co-precipitate the cations in the solution to obtain a composite oxide powder. The final product obtained by the existing co-precipitation method is doped with a large amount of ferroferric oxide. Ferroferric oxide is a paramagnetic material, which has a weak response to the magnetic field, a small magnetic susceptibility, and a weak magnetization effect. Once the external magnetic field is removed, the paramagnetic material cannot maintain its magnetism and cannot provide magnetic force for the agglomeration of the magnetic ion exchange resin. It is not suitable for the high-speed water treatment process of the suspended reaction layer. In addition, in the process of preparing magnetic iron oxide powder by the existing co-precipitation method, nitrogen protection needs to be introduced during the precipitation reaction to obtain the precursor. In actual industrial production, the cost is high, the process is complicated, the operation is difficult, and it is not suitable for the mass production of permanent magnetic materials.
[0003] Publication No. CN117247052A discloses a method for preparing magnetic ferroferric oxide by oxidation coprecipitation. The ferroferric oxide is prepared by oxidation coprecipitation, using a divalent iron source as a raw material and hydrogen peroxide as an oxidant to oxidize Fe2+ so that the molar ratio of Fe2+ to Fe3+ in the system is 1:2; then a precipitant is added to react under heating conditions to obtain nano-scale ferroferric oxide particles, hydrogen peroxide is mixed with an ammonium ferrous sulfate solution, sulfuric acid is added to adjust the pH value of the solution, and the solution is heated to a target temperature, and then a precipitant sodium hydroxide solution is added to adjust the pH value of the solution again. Under appropriate pH conditions, Fe2+ and Fe3+ in the system will precipitate simultaneously, and after standing and cooling for 10 minutes, ferroferric oxide nanoparticles with good magnetic responsiveness can be obtained; Publication No. CN115676899A discloses a method for preparing nano ferroferric oxide, comprising the following steps: mixing ferrous oxalate with an aqueous solution of a strong base for solid-liquid reaction to obtain a reaction solution, and the temperature of the solid-liquid reaction The reaction mixture is aged at 20 to 80°C and the aging time is 1 to 4 hours to obtain nano-iron tetroxide. Publication No. CN115159586A discloses an iron tetroxide magnetic powder for water treatment and a preparation method thereof. The preparation method comprises: preparing an iron salt solution and a precipitant solution, adding the solution to a reactor for coprecipitation reaction; stirring the solution for magnetization reaction to obtain a first slurry; classifying the first slurry to obtain a powder having a particle size smaller than the classified particle size and a second slurry containing magnetic particles; returning the powder to the reactor as a seed template for growth; washing the second slurry, spray drying, and obtaining iron tetroxide powder. The ferrite prepared by the above coprecipitation method is mostly iron tetroxide in the final product. Iron tetroxide is a paramagnetic material with a weak response to a magnetic field, a small magnetic susceptibility, and a weak magnetization effect. Once the external magnetic field is removed, the paramagnetic material cannot maintain its magnetism and cannot provide magnetic force for the agglomeration of magnetic ion exchange resins, and is not suitable for high-speed water treatment processes of suspended reaction layers.
[0004] Publication No. CN116692953A discloses a nano γ-Fe2O3 and a preparation method thereof, wherein ferrous oxalate and an aqueous hydrogen peroxide solution are mixed for oxidation reaction, and the obtained oxidation reaction liquid is mixed with an alkaline solution and then aged to obtain the nano γ-Fe2O3; the alkaline solution comprises an alkali metal hydroxide, an organic dispersant and water; Publication No. CN107572597A discloses a preparation method of a γ-Fe2O3 nanomaterial, wherein Fe(NO3)3•9H2O and L-tartaric acid are reacted in an aqueous phase to obtain a reddish-brown viscous liquid, the reddish-brown viscous liquid is placed in an air blast oven and dried to obtain a gray-green solid powder, the gray-green solid powder is placed in a muffle furnace and then roasted to obtain γ-Fe2O3 nanoparticles; the γ iron oxide obtained by the applicant using the above method is not easily modified in the process of preparing a magnetic ion exchange resin, and the obtained final product is of insufficient purity and contains a large amount of other oxides, such as paramagnetic materials such as ferroferric oxide and α-iron oxide, and is not suitable for high-speed water treatment processes of suspended reaction layers. Summary of the invention
[0005] In order to improve the above situation, the present invention provides a method for preparing a permanent magnetic material of an ion exchange resin for a high-speed water treatment process, which provides a method for obtaining active ferrous carbonate by double decomposition reaction between a carbonate solution and a ferrous salt solution, calcining until the active ferrous carbonate is completely decomposed into active ferroferric oxide, and causing the active ferroferric oxide to undergo oxidation reaction at a suitable temperature, and controlling the complete conversion of Fe3O4 into γ-Fe2O3. The final product has high purity, and the γ-iron oxide produced after calcination and oxidation is easily modified in the process of preparing the magnetic ion exchange resin, which is suitable for the high-speed water treatment process of the suspended reaction layer.
[0006] The present invention provides a method for preparing a permanent magnetic material of an ion exchange resin for a high-speed water treatment process, characterized in that the method comprises the following steps: (1) dissolving ferrous salt in water to prepare a ferrous salt solution with a concentration of 0.1-1 mol / L, and dissolving carbonate in water to prepare a carbonate solution with a concentration of 0.1-1 mol / L; Preferably, the ferrous salt is one or more of industrial grade FeSO4, FeSO4·7H2O, FeCl2, FeCO3, Fe3(PO4)2, Fe(NO3)2, Preferably, the carbonate is one of Na2CO3 and K2CO3; (2) Pumping the carbonate solution into the ferrous salt solution and stirring for 30-60 min, the carbonate solution and the ferrous salt solution undergo double decomposition reaction, and the mixed solution gradually turns into flocculent precipitation. The flocculent precipitation is centrifuged and filtered to remove excess water to obtain active ferrous carbonate precipitation; (3) Preliminarily placing dry ice in the ion exchange resin permanent magnetic material sintering furnace, loading the prepared activated ferrous carbonate precipitate into the ion exchange resin permanent magnetic material sintering furnace, heating the mixture to 200-250° C., and removing water from the activated ferrous carbonate; (4) After heating until the steam disappears, the temperature of the ion exchange resin permanent magnetic material sintering furnace is raised to 350-450°C for calcination until the active ferrous carbonate is completely decomposed into active ferrosoferric oxide, and then cooled to 200-250°C; (5) Air (oxygen) is introduced, and the active ferroferric oxide reacts with O2. The temperature is controlled at 300-500°C. Under this condition, Fe3O4 is converted into γ-Fe2O3. (6) After naturally cooling to room temperature, the mixture is taken out to obtain the permanent magnetic material γ-iron oxide. Beneficial Effects
[0007] 1. Through crystal form control, ferroferric oxide can be completely converted into γ-iron oxide after oxidation reaction, and the final product has high phase purity.
[0008] Second, the gamma iron oxide produced after calcination and oxidation is easily modified in the process of preparing magnetic ion exchange resin and is suitable for high-speed water treatment process of suspended reaction layer.
[0009] 3. The process is simple, easy to operate, and suitable for industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 The colors of the products at different calcination temperatures (a low temperature, b appropriate temperature, c high temperature).
[0011] Figure 2 These are the X-ray diffraction patterns of γ-Fe2O3 at low temperature, appropriate temperature and high temperature.
[0012] Figure 3 This is the hysteresis curve of γ-Fe2O3 at a suitable calcination temperature.
[0013] Figure 4 The hysteresis curves of two magnetic materials are (A) Fe3O4 and (B) Fe2O 3。 DETAILED DESCRIPTION Example
[0014] The present invention provides a method for preparing a permanent magnetic material of an ion exchange resin in a high-speed water treatment process, characterized in that it specifically comprises the following steps: (1) dissolving ferrous salt in water to prepare a ferrous salt solution with a concentration of 0.1-1 mol / L, and dissolving carbonate in water to prepare a carbonate solution with a concentration of 0.1-1 mol / L; The concentration of the ferrous salt solution is designed to be between 0.1-1mol / L. When the solubility of the ferrous salt solution is less than 0.1mol / L, the distance between the ferrous ions in the solution is relatively far, the active surface of the ferrous ions is large, and the contact opportunities with the oxygen dissolved in the water are increased. Therefore, nitrogen must be introduced for protection in the process of dissolving the ferrous salt in water, otherwise the ferrous salt solution is prone to oxidation reaction with oxygen in the air, and the ferrous ions are reduced to ferric ions; In addition, the increase in concentration will accelerate the reaction rate. In the ferrous salt solution with a concentration greater than 1mol / L, the oxidation reaction is more rapid, and after the ferrous ions are oxidized to ferric ions, the ferric ions can further catalyze the oxidation reaction of nearby ferrous ions, so nitrogen protection is also required during the preparation process, and the ferrous salt solution with a concentration greater than 1mol / L will rapidly generate precipitation products when undergoing double decomposition reaction with the carbonate solution, and the precipitation products will rapidly aggregate, which is likely to cause the reaction system to be unstable, causing local overheating or uneven reaction, affecting the generation of active ferrous carbonate; Preferably, during the process of dissolving the ferrous salt in water, the stirring speed is between 100-500 rpm; When the stirring speed is higher than 500rpm, the turbulence and splashing on the liquid surface increase, causing more air (oxygen) to contact the ferrous salt solution, which is prone to oxidation. When the stirring speed is lower than 100rpm, the low-speed stirring cannot generate enough shear force and fluidity to break the cohesion between the solid ferrous salt particles. The particles are easy to aggregate and difficult to disperse evenly, reducing the concentration uniformity of the liquid. The design of dissolving ferrous salt in water to prepare ferrous salt solution and dissolving carbonate in water to prepare carbonate solution, using ordinary water instead of deionized water, can significantly reduce production costs, simplify operation procedures, and reduce equipment requirements in industrial production. In addition, during the double decomposition reaction, trace ions in ordinary water can buffer the impact of external pollutants on the reaction system and improve the stability of the reaction process. Preferably, the ferrous salt is one or more of industrial grade FeSO4, FeSO4·7H2O, FeCl2, FeCO3, Fe3(PO4)2, Fe(NO3)2, Preferably, the carbonate is one of Na2CO3 and K2CO3; (2) Pumping the carbonate solution into the ferrous salt solution and stirring for 30-60 min, the carbonate solution and the ferrous salt solution undergo double decomposition reaction, and the mixed solution gradually turns into flocculent precipitation. The flocculent precipitation is centrifuged and filtered to remove excess water to obtain active ferrous carbonate precipitation; Preferably, during the double decomposition reaction between the carbonate solution and the ferrous salt solution, no nitrogen protection is required, the cost is low, the operation is easy, and it is suitable for industrial production; Preferably, during the double decomposition reaction between the carbonate solution and the ferrous salt solution, the dripping speed of the carbonate solution is controlled so that the pumping time is not less than 10 min, so as to control the particle size of the generated product to be less than nm. Preferably, during the composite reaction, the reaction ratio of the carbonate solution to the ferrous salt solution is 1-1.2:1 (mol ratio). The gamma iron oxide prepared by the active ferrous carbonate precipitate generated by the reaction within this range is convenient for modification in the subsequent preparation of the magnetic ion resin material, and the economic cost is low; and the solution ratio of the carbonate solution to the ferrous salt solution within this range can maintain the pH during the reaction, and no additional acid or alkali is needed to adjust and control the pH value during the reaction, which has low cost, simple process, simple operation, and is easy for industrial production; (3) Preliminarily placing dry ice in the ion exchange resin permanent magnetic material sintering furnace, loading the prepared activated ferrous carbonate precipitate into the ion exchange resin permanent magnetic material sintering furnace, heating the mixture to 200-250° C., and removing water from the activated ferrous carbonate; Since it takes a certain amount of time to load the active ferrous carbonate, the design of pre-placing dry ice in the ion exchange resin permanent magnetic material sintering furnace can isolate the active ferrous carbonate in the sintering furnace to prevent it from being oxidized during the waiting process. The solid dry ice is easy to operate during the loading process, and during the heating process, the dry ice sublimates into carbon dioxide gas and is discharged, so there will be no residue and no new impurities will be introduced, thereby ensuring the purity of the active ferrous carbonate. (4) After heating until the steam disappears, the temperature of the ion exchange resin permanent magnetic material sintering furnace is raised to 350-450°C for calcination until the active ferrous carbonate is completely decomposed into active ferrosoferric oxide, and then cooled to 200-250°C; Preferably, during the calcination process, the rotation speed of the ion exchange resin permanent magnetic material sintering furnace is 1-2 rpm. At this rotation speed, the movement of the active ferrous carbonate particles is relatively stable, and the active ferrous carbonate is prevented from agglomerating into balls due to high-speed movement and collision. At the same time, the rotation speed helps to maintain the dispersed state of the active ferrous carbonate particles and accelerate the decomposition rate of the active ferrous carbonate. Preferably, during the calcination process, the active ferrous carbonate is decomposed into active ferrosoferric oxide and gases CO and CO2, and the gases are discharged out of the sintering furnace. When the CO concentration is zero, it means that the active ferrous carbonate is completely decomposed; (5) Air (oxygen) is introduced, and the active ferroferric oxide reacts with O2. The temperature is controlled at 300-500°C. Under this condition, Fe3O4 is converted into γ-Fe2O3. Preferably, the steps (1) to (4) generate active ferroferric oxide that can be used in step (5). The applicant has found in repeated experiments that γ iron oxide cannot be generated by directly calcining ordinary ferroferric oxide products with stable crystal form with oxygen, and γ iron oxide cannot be generated by directly calcining active ferroferric oxide with unstable crystal form purchased from outside with oxygen under the same conditions. During the reaction of the active ferroferric oxide and oxygen, the temperature is controlled at 300-500°C. When the temperature is lower than 300°C, the main body of the final product generated by calcination is ferroferric oxide. When the temperature is higher than 500°C, the main body of the final product generated by calcination is α-iron oxide. Both ferroferric oxide and α-iron oxide are paramagnetic materials and cannot be used for the preparation of magnetic ion exchange resins. The specific results are as follows: Figure 1 shown.
[0015] from Figure 1 It can be seen that the color of the low-temperature calcined product is brown-black, and the main body is Fe3O4, which means that the temperature is too low and part of Fe3O4 has not been converted into γ-Fe2O3; the color of the product calcined at the appropriate temperature is brown-yellow, which is very close to the color of γ-Fe2O3 in theory. It is speculated that the product calcined at this temperature is closer to the ideal product; the color of the product calcined at high temperature is reddish brown, which means that the temperature is too high and part of γ-Fe2O3 will be converted into red ɑ-Fe2O3; In order to determine the phase types of samples obtained at different calcination temperatures, X-ray diffractometer (XRD) was used to analyze the Figure 1 The products a, b, and c were characterized, such as Figure 2 shown.
[0016] from Figure 2It can be observed that the positions of the characteristic peaks of the three samples are basically consistent, and characteristic peaks appear at 2θ=30.3°, 35.7°, 43.4°, 53.8°, 57.3°, and 63°, which correspond to the six characteristic peaks of the standard card of γ-Fe2O3 at 2θ=30.241°, 35.630°, 43.284°, 53.733°, 57.271°, and 62.925°, indicating that the main phase in the three magnetic materials is γ-Fe2O3; however, the characteristic peak height of the sample calcined at the appropriate temperature is higher and the relative intensity is higher, that is, the higher the degree of crystallization, indicating that the γ-Fe2O3 phase in the sample is relatively pure, and the characteristic peak intensity of the samples calcined at low and high temperatures is relatively low, which may contain impurity phases, such as Figure 3 shown.
[0017] from Figure 3 The hysteresis curve of the γ-Fe2O3 magnetic material is shown in Figure 1. The hysteresis curve does not pass through the zero point, the specific saturation magnetic intensity is 71.23emu / g, and the residual magnetization intensity is 16.24emu / g, indicating that the material is a permanent magnetic material; there are unpaired electrons in the 3d orbit of Fe, and the 3d electron orbit induces polarization of the surrounding O-2p state spin electrons. The 2p orbit of O hybridizes with the 3d orbit of Fe, resulting in the spin polarization of the electronic state at the Fermi energy, so that the system produces a net magnetic moment and exhibits permanent magnetism; In order to compare the magnetic properties of Fe3O4 and γ-Fe2O3 materials, a vibrating magnetometer was used to analyze and characterize them. The hysteresis curves obtained are shown in Figure 4 shown.
[0018] from Figure 4 The hysteresis curves of the two magnetic materials can be observed. The hysteresis curve of Fe3O4 passes through the zero point, the specific saturation magnetic intensity is 60.61 emu / g, and the residual magnetization intensity is 0 emu / g, indicating that the prepared Fe3O4 magnetic nanoparticles are paramagnetic materials; while the hysteresis curve of γ-Fe2O3 does not pass through the zero point, the specific saturation magnetic intensity is 66.47 emu / g, and the residual magnetization intensity is 24.43 emu / g, indicating that the prepared γ-Fe2O3 is a permanent magnetic material. (6) After naturally cooling to room temperature, the mixture is taken out to obtain the permanent magnetic material γ-iron oxide.
[0019] The permanent magnetic material precursor is ferrous carbonate, which is prepared by the reaction of ferrous salt and carbonate solution. The ferrous salt and carbonate used in the whole process are of low cost, and the reaction process is controllable, which reduces unnecessary waste and thus reduces production costs. The design of the calcination temperature in the rotary kiln is 300-600°C, which requires less heat and reduces energy consumption compared with other methods such as sol-gel method; The purpose is to obtain active ferrous carbonate by double decomposition reaction between carbonate solution and ferrous salt solution, then calcine until the active ferrous carbonate is completely decomposed into active ferroferric oxide, and make the active ferroferric oxide undergo oxidation reaction at a suitable temperature to control the complete conversion of Fe3O4 into γ-Fe2O3.
[0020] It should be noted that, unless otherwise clearly specified and limited, the terms "placed", "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection method such as a folding connection, a rivet connection, a pin connection, a bonding connection and a welding connection, or a detachable connection method such as a threaded connection, a snap connection and a hinge connection, or an integral connection, or an electrical connection, or a direct connection, or an indirect connection through an intermediate medium, or the internal connection of two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
Claims
1. A method for preparing a permanent magnetic material of an ion exchange resin for a high-speed water treatment process, characterized in that The following steps are involved: (1) dissolving ferrous salt in water to prepare a ferrous salt solution with a concentration of 0.1-1 mol / L, and dissolving carbonate in water to prepare a carbonate solution with a concentration of 0.1-1 mol / L; (2) Pumping the carbonate solution into the ferrous salt solution and stirring for 30-60 min, the carbonate solution and the ferrous salt solution undergo double decomposition reaction, and the mixed solution gradually turns into flocculent precipitation. The flocculent precipitation is centrifuged and filtered to remove excess water to obtain active ferrous carbonate precipitation; (3) Put dry ice in the permanent magnetic material sintering furnace in advance, put the prepared activated ferrous carbonate precipitate into the permanent magnetic material sintering furnace, heat it to 200-250°C, and remove the water in the activated ferrous carbonate; (4) After heating until the steam disappears, the permanent magnetic material sintering furnace temperature is raised to 350-450°C for calcination until the active ferrous carbonate is completely decomposed into active ferrosoferric oxide, and then cooled to 200-250°C; (5) Air (oxygen) is introduced, and the active ferroferric oxide reacts with O2. Under this condition, Fe3O4 is converted into γ-Fe2O3; (6) After naturally cooling to room temperature, the mixture is taken out to obtain the permanent magnetic material γ-iron oxide.
2. The method for preparing a high-speed water treatment process ion exchange resin permanent magnetic material according to claim 1, characterized in that The steps (1) to (4) generate active ferrosoferric oxide for use in step (5).
3. The method for preparing a high-speed water treatment process ion exchange resin permanent magnetic material according to claim 1, characterized in that During the process of dissolving the ferrous salt in water, the stirring speed is between 100-500 rpm.
4. The method for preparing a high-speed water treatment process ion exchange resin permanent magnetic material according to claim 1, characterized in that During the double decomposition reaction between the carbonate solution and the ferrous salt solution, there is no need to introduce nitrogen protection.
5. The method for preparing a high-speed water treatment process ion exchange resin permanent magnetic material according to claim 1 or 4, characterized in that During the composite reaction, the reaction ratio of the carbonate solution to the ferrous salt solution is 1-1.2:1 (mol ratio).
6. The method for preparing a high-speed water treatment process ion exchange resin permanent magnetic material according to claim 1, characterized in that The ferrous salt is one or more of industrial grade FeSO4, FeSO4·7H2O, FeCl2, FeCO3, Fe3(PO4)2, Fe(NO3)2, and the carbonate is one of Na2CO3 and K2CO3.
7. The method for preparing a high-speed water treatment process ion exchange resin permanent magnetic material according to claim 1, characterized in that During the calcination process, the rotation speed of the permanent magnetic material sintering furnace is 1-2 revolutions per minute.
8. The method for preparing a high-speed water treatment process ion exchange resin permanent magnetic material according to claim 1, characterized in that During the calcination process, active ferrous carbonate is decomposed into active ferrosoferric oxide and gases CO and CO2, and the gases are discharged out of the sintering furnace. When the CO concentration is zero, it means that the active ferrous carbonate is completely decomposed.
9. The method for preparing a high-speed water treatment process ion exchange resin permanent magnetic material according to claim 1, characterized in that During the double decomposition reaction between the carbonate solution and the ferrous salt solution, the dripping speed of the carbonate solution is controlled so that the pumping time is not less than 10 minutes.
10. The method for preparing a permanent magnetic material of an ion exchange resin for a high-speed water treatment process according to claim 1, wherein during the reaction of the active ferroferric oxide and oxygen, the temperature is controlled at 300-500°C.
Citation Information
Patent Citations
Preparation method of gamma-Fe2O3 nano material
CN107572597A
Ferroferric oxide magnetic powder for water treatment and preparation method thereof
CN115159586A
Preparation method of nano ferroferric oxide
CN115676899A
Nanometer gamma-Fe2O3 and preparation method thereof
CN116692953A
Method for preparing magnetic ferroferric oxide through oxidation coprecipitation
CN117247052A